Upaya Peningkatan Kemampuan Siswa dalam Menggunakan Aplikasi Myob Accounting di SMK Negeri 1 Belitang Madang Raya - Miftakhur Rohmah; Tri Ratna Dewi; Khusnatul Amaliah; Sutati Sutati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
Computer accounting is one of the subjects that is an important part of the connection with the industrial revolution 4.0. The development of this era requires teachers and students to be able to carry out learning processes that is oriented to technology that is adapted to the industrial world environment as a target of students' self-development. The perceived benefit of understanding MYOB Accounting is that we can automate bookkeeping in a complete, detailed, and accurate manner. MYOB is easy to understand and learn. Likewise with the functions it has, the explanation is very clear. The field of accounting activities in the current era is developing in the process and implementation. The importance of the skills is possessed by students in preparing for the Competency Examination and preparing for the world of work, this is a reason for the need for appropriate and appropriate learning to hone the abilities of students.